2007
DOI: 10.1021/ac061380v
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Spring Constant of Atomic Force Microscopy Cantilevers by Finite Element Method

Abstract: Atomic force microscopy (AFM) probe with different functions can be used to measure the bonding force between atoms or molecules. In order to have accurate results, AFM cantilevers must be calibrated precisely before use. The AFM cantilever's spring constant is usually provided by the manufacturer, and it is calculated from simple equations or some other calibration methods. The spring constant may have some uncertainty, which may cause large errors in force measurement. In this paper, finite element analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…To capture mode coupling in the high-frequency behavior in an AFM cantilever, it is important to include terms related to torsional motion in the equation of motion. It is generally difficult to analytically solve the equation of motion for such a case, while it can be computationally tractable using finite element methods [73]. The topic of mode-coupling in the vibrational dynamics of micro/nanocantilevers has been recently received special attention because the mode-coupling has been found to improve the AFM imaging quality [74][75][76].…”
Section: Eimentioning
confidence: 99%
“…To capture mode coupling in the high-frequency behavior in an AFM cantilever, it is important to include terms related to torsional motion in the equation of motion. It is generally difficult to analytically solve the equation of motion for such a case, while it can be computationally tractable using finite element methods [73]. The topic of mode-coupling in the vibrational dynamics of micro/nanocantilevers has been recently received special attention because the mode-coupling has been found to improve the AFM imaging quality [74][75][76].…”
Section: Eimentioning
confidence: 99%
“…Clifford et al [98] showed the modification of the solution proposed by Neumaister and Ducker [97] where match level of 1% was obtained. Also Chen et al developed this particular approach [99]. They presented the impact of various factors on the calculation uncertainty such as: Poisson factor, the cantilever's thickness variation, mass of the tip, the tilt angle and presence of the non-axial mass causing torsional forces.…”
Section: Finite Elements Analysis (Finite Elements Method)mentioning
confidence: 99%
“…Many methods were proposed to obtain the bending spring constant k z and the torsional spring constant k t of rectangular or V-shaped cantilevers. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] All the existing methods used to obtain the cantilever spring constant with the shape of rectangular or V-shaped geometries assumed an equivalent isotropic property of the AFM cantilever. Based on this assumption, the bending spring constant k z of the rectangular cantilever can be expressed as 4,[6][7][8] …”
mentioning
confidence: 99%
“…Detailed discussions on the constraint of the aforementioned equations have been made in our previous study. 11 To eliminate the limitation of regular geometry and dimensional uncertainty from fabrication, Cumpson and co-workers 13,14 used the microfabricated array of reference spring ͑MARS͒ and the lateral electrical nanobalance ͑LEN͒ devices to find the bending spring constant k z and the lateral spring constant k y of the AFM cantilever directly, and the errors of the MARS and the LEN devices are estimated at 5% and 7%, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation